Construction of The Distribution of Government Authorities - Salmon, Hendrik (SASI, 2023)
Introduction: The concept of dividing government affairs into de-centralization and co-administration has a long history in Indonesian constitutional records.Purposes of the Research: One of the issues regarding the constitutionality of regional government which has become a space for academic debate after the publication of Law Number 23 of 2014 is related to the concept of dividing government affairs between government structures. Moving on from the perspective of State Administrative Law and Administrative Law, the analysis will be directed at the parameters used to construct the division of authority between government structures based on executive power or based on the authority established by the constitution.Methods of the Research: The research method in this paper uses a normative juridical research type, namely the process to find the rule of law, legal principles and legal doctrine to answer the legal issues faced. By using the research approach statue approach (approach of Act), conceptual approach (conceptual approach), philosophical approach and sociological approach as a supporting approach.Results of the Research: Amendments to the 1945 Constitution, especially the second amendment regarding the concept and pattern of division of government, have indicated that a centralized government will actually be a threat to disintegration, so that strengthening decentralization is not weakening Indonesianness but an effort to strengthen it. In other words, the choice to use the concept of autonomy as broadly as possible should be understood as a way to build a just balance of central and regional power relations. The regional government law has reduced the essence of the concept of deconcentration where previously it was only carried out by the Governor, now it is also carried out by the Regent/Mayor, in such a concept, the problem is how to juxtapose the decentralization method with other methods such as deconcentration and assistance and institutional tasks for the three the principle.